Oil well pipes and oil well pipe thread joints

The resin coating with an alkali soap layer addresses the issue of damage to solid lubricating coatings during the initial engagement stage of oil well pipe threaded joints, enhancing lubrication and rust prevention and improving galling resistance.

JP7656086B2Active Publication Date: 2025-04-02JFE STEEL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023570234
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-08-14
Publication Date
2025-04-02
Estimated Expiration
2043-08-14

AI Technical Summary

Technical Problem

Existing solid lubricating coatings for oil well pipe threaded joints are prone to damage during the initial engagement stage due to eccentricity and swinging of the oil well pipe, leading to reduced galling resistance during tightening.

Method used

A resin coating with an alkali soap layer is formed on the surface of the threaded portion of the oil well pipe, which reduces damage to the solid lubricating coating during the initial engagement stage and enhances lubrication and rust prevention properties.

Benefits of technology

The resin coating with an alkali soap layer effectively reduces damage to the solid lubricating coating, improves lubrication performance, and provides excellent rust prevention, leading to increased galling resistance and prolonged service life of the oil well pipe screw joint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656086000002
    Figure 0007656086000002
  • Figure 0007656086000003
    Figure 0007656086000003
  • Figure 0007656086000004
    Figure 0007656086000004
Patent Text Reader

Abstract

Provided is an oil well pipe screw joint having a solid lubrication coat having excellent lubrication and anti-rust properties. This oil well pipe constitutes a box (2) having a female screw or a pin (1) having a male screw that is used in the oil well pipe screw joint formed by linking the box (2) to the pin (1). The outermost layer of a screw section has a resin coat constituted of a binder resin containing an alkaline soap as a solid lubricant. The resin coat has an alkaline soap layer on the surface thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to technology relating to an oil well pipe having a threaded portion provided with lubricity and rust resistance by a solid lubricant coating, an oil well pipe threaded joint using the same, and a paint for forming the outermost layer (top coat layer) of the threaded portion. The paint may be used to repair a lubricating film formed on the threads of an oil country tubular good. [Background technology]

[0002] In the case of oil well pipe thread joints, a viscous lubricant called a compound is generally applied to the threads to form a wet lubricating film before tightening. Most of these compounds contain heavy metals such as Pb and Zn. In recent years, environmental pollution has become a problem, and lubricants that do not contain heavy metals have been increasingly used to lubricate threads. However, as long as wet lubricants are used, the following problems remain. For example, when used in the desert, if sand flies in and adheres to the threads of the oil well pipes, there is a risk of seizure occurring when tightening the threaded joint. In addition, when used in cold regions, there is a problem that wet lubricants freeze and are difficult to apply.

[0003] To address these issues, there is a technology that uses a dry solid lubricant coating that does not contain heavy metals to lubricate the threads of oil country tubular goods. Technologies that use solid lubricant coatings on oil country tubular goods include those described in Patent Documents 1 to 3, for example. Patent Document 1 discloses a double coating consisting of a viscous liquid or semi-solid lubricating coating and a dry solid coating formed thereon. Patent Document 1 states that this configuration provides an oil well pipe threaded joint with not only rust prevention and seizure resistance, but also resistance to foreign matter adhesion. Patent Document 1 also states that the lubricant must contain at least an alkaline earth metal salt of a fatty acid. Patent Document 1 also states that a component selected from an organic resin, an oil agent, and an additive may be blended to improve the uniform dispersion of the alkaline earth metal salt of a fatty acid.

[0004] In Patent Document 2, a solid lubricant coating with a high friction coefficient is formed on a part of the metal contact portion. In Patent Document 2, a viscous liquid lubricant coating or a solid lubricant coating with a low friction coefficient is formed on at least one of the surfaces of the portion other than the contact surface and the contact surface of the mating member. Patent Document 2 states that this configuration realizes a large torque-on-shoulder resistance. Patent Document 2 also describes rosin-based substances, waxes, metal soaps, and basic aromatic organic acid metal salts as preferred examples of the viscous liquid lubricant coating. Patent Document 2 also defines metal soaps as salts of fatty acids with metals other than alkali metals. Patent Document 2 also states that this configuration is effective in enhancing the anti-seizure and anti-rust effects of the coating.

[0005] Patent Document 3 describes forming a lubricating film by applying a lubricating film-forming composition to the mating surface of either the box or the pin that constitutes a threaded joint. The lubricating film-forming composition is formed by dissolving one or more basic oils selected from basic sulfonates, basic salicylates, and basic phenates in a solvent. Patent Document 3 describes that this composition provides good rust prevention and lubricity. Patent Document 3 also describes that a thermoplastic resin powder may be included to further improve seizure resistance. Patent Document 3 also describes that an alkaline earth metal salt or an alkali metal salt of a fatty acid may be included as a diluent of the basic oil.

[0006] All of the above documents contain descriptions of solid lubricant coatings for threaded joints of oil country tubular goods. On the other hand, solid lubrication techniques in fields other than the field of oil well pipe threaded joints are described in, for example, Patent Documents 4 and 5. Patent Document 4 discloses an invention related to a lubricant used when drawing a metal workpiece with a die. Patent Document 4 describes the following advantages of a lubricant for dry wire drawing that contains an alkali metal soap. That is, the first advantage is that a coating with excellent lubricity is formed. The second advantage is that the coating is water-soluble, so that the lubricant can be easily removed before plating or heat treatment.

[0007] On the other hand, Patent Document 4 lists a drawback of dry wire drawing lubricants containing alkali metal soaps, which is that when exposed to high temperatures, they liquefy and the lubricant's required followability and spreadability on wire rods decrease. In contrast, Patent Document 4 describes adding a certain amount of unsaturated fatty acid metal soap or alkali soap, which is prone to intermolecular polymerization reactions, to saturated fatty acid metal soap or alkali soap. This description is for severe wire drawing conditions under high temperature, high pressure, and high speed. Patent Document 4 also describes that according to this configuration, a dry wire drawing lubricant that exhibits lubricity, peeling resistance, heat resistance, and high-temperature spreadability can be obtained even under the above-mentioned severe conditions. The lubricant described in Patent Document 4 is completed by drying the blended predetermined components. The lubricant is then crushed into a solid, powder, or granular form and then dropped into a dice box for use.

[0008] Patent Document 5 also discloses an invention related to a steel wire having a lubricating coating on its surface. Patent Document 5 describes that, as one of the prior art, a composite coating (chemical conversion coating) consisting of a zinc phosphate coating and a soap layer has high workability and corrosion resistance. On the other hand, Patent Document 5 describes that in recent years, from the viewpoint of environmental conservation, a lubricating coating that does not contain phosphorus has been required. Patent Document 5 also describes that silicon, tungsten, and an alkali metal salt of a fatty acid are blended in a predetermined ratio. Patent Document 5 also describes that, according to the composition, a lubricating coating having high workability and corrosion resistance can be obtained even without containing phosphorus. Here, the alkali metal salt of a fatty acid is blended to reduce friction of the lubricating coating and prevent poor heading appearance. And, it is described that the alkali metal salt is water-soluble, so that water evaporates to form the coating. And, Patent Document 5 also describes that, when the coating is formed, the alkali metal salt precipitates finely and uniformly, so that local differences in wear state are unlikely to occur, and a good heading appearance can be obtained. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Special Publication No. 2008-537062 [Patent Document 2] JP 2013-108556 A [Patent Document 3] JP 2002-173692 A [Patent Document 4] JP 2009-132811 A [Patent Document 5] JP 2017-66515 A Summary of the Invention [Problem to be solved by the invention]

[0010] The present inventors found that in actual well tightening of oil well pipe threads, cases are often observed in which the pin thread is rotated by power tongs when the pin thread and the box thread are not fully engaged. The present inventors then discovered that tightening is performed in the following two steps, and that the galling resistance is reduced in the case of a solid lubricant coating. That is, the solid lubricant coating formed on the threaded portion constituting the threaded joint is damaged by the eccentricity and whirling of the oil well pipe at the stage (step 1) when the threads are not engaged. As a result, they discovered a phenomenon in which the galling resistance is reduced in the tightening step (step 2) after the threads are engaged.

[0011] Next, we will provide a supplementary explanation of this finding. When considering actual wells, it is necessary to assume that the solid lubricant coating will inevitably be scraped off to a certain extent when tightening and undoping. The inventors have found that the scraped off pieces have been the cause of seizure problems in the past. For this reason, the inventors have found that unless the lubricity of the solid lubricant coating is evaluated in an actual well or under conditions similar to those of an actual well, the evaluation will be meaningless in an actual well.

[0012] Here, a conventional test that has been frequently used is a fastening test in a laboratory using a short pin of about 1 m. In this fastening test, in the case of the lubrication of the solid lubricant coating that is the subject of the present disclosure, if the result is NG, the result will also be NG in an actual well. However, the inventors have found that even if the evaluation in the test using this conventional short pin is OK, that does not guarantee that the result will be OK in an actual well. In addition, in the case of viscous liquid lubricating compounds, because they are wet, there is not much difference between the tightening and tightening evaluation using short pins in the lab and the actual situation in the well. The judgment in the actual well tends to be linked to the evaluation in the lab. It is assumed that the viscous liquid lubricating compounds move in conjunction with the tightening when tightening and tightening.

[0013] On the other hand, in the case of a solid lubricating coating, the debris that is inevitably scraped off does not necessarily move in conjunction with tightening and loosening. For this reason, in an actual well where debris is inevitably generated in large amounts, the debris is likely to cause clogging. In addition, it was found that when significant peeling occurs, seizure occurs in the areas where the solid lubricating coating has become thin or has disappeared. From this knowledge, the inventors have come to the realization that evaluation of solid lubricating coatings must be carried out taking this into account.

[0014] This finding will now be explained in more detail. In an actual well, the situation in which a full-length pin thread is tightened into a box thread is not carried out under the ideal conditions described in textbooks. In the ideal state, one would imagine that a full-length pin is set upright in the box thread, fitted into it, and tightened straight. However, in reality, this is not the case. The structure of OCTG threads has an incomplete thread part when the pin thread is inserted into the box thread, and there are many cases in which the pin is set slightly obliquely during initial setting due to the play (play, margin) of that part. And when the threads are first tightened, the pin threads move around by the play. For this reason, the weight of the pin (large load) and the unbalanced load caused by the uneven movement of the pin are superimposed on the solid lubricating coating before the threads engage with each other. And, there is a high concern that the solid lubricating coating will be abnormally scraped off or completely peeled off.

[0015] This is specifically shown in Figures 3 and 4. The examples shown in Figures 3 and 4 are examples where the tightening and tightening test conditions were 15 to 25 rpm until the torque was generated, and then 2.5 to 1.5 rpm after the torque was generated. This is the result of testing under more severe conditions (faster rotation speed) than the conditions specified in the screw handling instructions (tightening instructions in the technical package). The examples shown in Figures 3 and 4 are examples where the well tightening material and strength grade are 9-5 / 8” 53.5# Q125 material, JFELION TM This is an example of the evaluation of a solid lubricant coating on a screw.

[0016] Figure 3 shows the torque turn chart when a short pin of about 1m is used and tightened with vertical power tongs based on the conventional laboratory evaluation method. Because the pin is short, handling is not difficult, the pin can be set straight, and the pin thread can be set by hand until it is almost completely unexposed (Figure 3(b)). In this case, the torque turn chart shows that the torque starts to rise from the beginning of tightening and is tightened beyond the bending point of the shoulder torque. In other words, in this case, it becomes a very ordinary chart (Figure 3(a)). The reason that the torque rises immediately here is because the pin thread and the box thread are fully engaged at the initial setting stage and tightening is performed from the preset position.

[0017] On the other hand, Figure 4 shows the torque-turn chart for Range-3, that is, when one actual-size pin of just over 40 feet (just over 12 m) is used, and is the result of a test in a simulated well. Here, the units (size) of the horizontal axis are different from those in Figure 3. Note that the simulated well is not an actual well producing oil or gas, but an experimental well with a simulated hole so that just over three actual-size pins can enter underground (downward). At the same time, the shed has a rig that can hang and set about two to three connected pins, and it means a group of equipment and an experimental facility that can perform tightening and tightening tests. This case shows the tendency in a situation where the pins are set in the same way as in an actual well, but it is different from the case of Figure 3 with a short pin. In this example, a steady torque does not occur until about 6.3 rotations, and spike-like torque is sometimes observed irregularly during this rotation. This phenomenon is directly linked to damage to the solid lubricant coating, and it was found that it suggests that it is important to evaluate the solid lubricant coating based on this fact.

[0018] The torque chart example in Figure 4 shows what happens when a Range-3 pin, that is, a pin of just over 40 feet (just over 12 m), is set and tightened. In this case, because it is a full-sized pin (about 12 m), it is almost always impossible to set the pin completely straight, and the pin is inserted at a slight angle. This is the same condition as in the case of an actual well. For this reason, even if the pin is set by hand tightening, the pin thread and the box thread will partially hit each other too strongly. For this reason, five or more threads of the pin, in many cases about half of the total threads, will be exposed from the box when tightened by hand, and it will not go any further. From that state, tightening with tongs begins. And in most cases, the threads are not fully engaged with each other, and some parts hit each other carelessly too hard, preventing it from going any further. For this reason, with full-sized pins, the box thread and the pin thread will hit each other in an unbalanced state before the threads are fully engaged with each other. In other words, this means that they will cause damage to each other. With this in mind, we have come to the realization that, without evaluation of the solid lubricant coating, as already mentioned above, if something is NG in the evaluation using a short pin, it will be NG in an actual well, but if it is OK in the evaluation using a short pin, it does not necessarily mean it will be OK in an actual well. For this reason, we have come to the realization that in the past inventions, in the upper and lower limit regulations for components, conditions, and other parameters, evaluations based on OK in the short pin evaluation do not necessarily intend a good range in an actual well.

[0019] Patent Documents 1 to 3 all relate to solid lubrication technology for oil well pipe threaded joints. However, Patent Documents 1 to 3 are assumed to be examples of test evaluations using short pins. For this reason, Patent Documents 1 to 3 leave room for improvement in terms of reducing damage to the solid lubricant coating in step 1. On the other hand, Patent Documents 4 and 5 are related to the use of solid lubricants in technical fields other than the oil well tubular goods field, and relate to lubrication applications in metal plastic processing. In other words, Patent Documents 4 and 5 do not state anything about conversion to the oil well tubular goods field.

[0020] Here, in Patent Document 4, metal soap or alkali soap is used as a solid lubricant. However, the technology of Patent Document 4 assumes that the lubricant is in a solid, powdered or granular form and is applied to a dry environment for use. For this reason, the technology of Patent Document 4 is not intended to be used for oil well pipe threads. For example, even if the solid lubricant described in Patent Document 4 is applied to an oil well pipe thread that is set vertically, the solid lubricant will fall and will not be retained on the surface of the threaded portion.

[0021] In addition, in Patent Document 5, a lubricating film containing an alkaline soap is formed on the surface of a steel material by applying a specific chemical solution to the steel material and then evaporating the water as a solvent. However, when this method is applied to the tightening work of oil well pipe threads, the following problem occurs. That is, the water-soluble alkaline soap applied to the threads of the oil well pipe is easily washed away by rainfall or backflow of muddy water from inside the well. As a result, in the field of oil well pipes, the method described in Patent Document 5 cannot maintain lubricity. Furthermore, oil well pipe threads are required to have strong corrosion resistance so that they do not rust even when stored outdoors for several years. However, alkaline soaps are generally recognized as being undesirable from the viewpoint of corrosion resistance because they attract water due to their deliquescence. However, in reality, Patent Document 4 does not require rust prevention. Furthermore, Patent Document 5 only requires rust prevention that can withstand indoor storage for only two months.

[0022] The present invention has been made in view of the above-mentioned points, and has as its object to provide a threaded joint for oil country tubular goods having a solid lubricant coating which has excellent lubricity and rust prevention properties. [Means for solving the problem]

[0023] As the inventors described above have found, in the make-up of an oil well pipe threaded joint, at the stage (step 1) when the threads of the pin and box are not engaged, rattle, i.e., eccentricity and whirling of the oil well pipe, occurs. This rattle causes damage to the solid lubricant coating formed on the threads. The inventors have found that in order to suppress this damage, it is effective to form an alkali soap layer directly on the thread surface of at least one of the pin or box, or on the solid lubricant coating. Here, the alkaline soap in the present disclosure refers to a salt of a fatty acid and an alkali metal such as sodium or potassium, and is to be distinguished from metal soaps, which are salts of fatty acids and metals other than alkali metals.

[0024] Conventionally, when soap is used as a solid lubricant for threaded joints of oil well pipes, metal soaps have been used, and alkali soaps have not attracted attention. This is because, as mentioned above, alkali soaps are water-soluble and have poor waterproofing and rust prevention properties. Also, metal soaps are easier to disperse than general binder resins. However, the inventors discovered that adding an alkaline soap to the solvent in which the resin is dissolved results in the formation of an alkaline soap layer on the surface of the resin coating, which is effective in reducing the rattle described above. Based on this finding, the inventors have developed the present invention.

[0025] In order to solve the problems, one aspect of the present invention is an oil country pipe used in an oil country pipe threaded joint formed by connecting a box having a female thread and a pin having a male thread, the box or pin being a component of the box, the outermost layer of the threaded portion having a resin coating containing an alkali soap as a solid lubricant in a binder resin, and the resin coating having an alkali soap layer formed on the surface. Another aspect of the present invention is an oil well pipe threaded joint formed by connecting a box having a female thread and a pin having a male thread, wherein at least one of the box and the pin is made of an oil well pipe according to one aspect of the present invention. Effect of the Invention

[0026] According to one aspect of the present invention, by forming a resin layer having alkaline soap dispersed on the surface side as the outermost layer of the threaded portion of an oil well pipe, it is possible to provide an oil well pipe threaded joint having a solid lubricant coating with excellent lubricity and rust resistance with a simple configuration. [Brief description of the drawings]

[0027] [Figure 1] FIG. 1 is a diagram showing an oil well pipe and an oil well pipe threaded joint. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of the configuration of a lubricating coating formed on a threaded portion. [Diagram 3] FIG. 1A is an example of a tightening chart in a conventional laboratory test, and FIG. 1B is a diagram showing an example of an initial set position in that test. [Figure 4] FIG. 1A is an example of a tightening chart for an actual well, and FIG. 1B is a diagram showing an example of the initial set position. [Diagram 5] Schematic diagrams of fastening charts, where (a) is for an actual well and (b) is for a conventional laboratory test. [Figure 6] FIG. 1 is a diagram illustrating new laboratory test conditions (weight tongs). [Figure 7] FIG. 13 is a diagram showing an example of weight placement under new laboratory test conditions (weight tongs). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Next, an embodiment of the present invention will be described with reference to the drawings. This disclosure relates to a coating structure formed on the fastening surfaces of the threads of oil country tubular goods used in actual oil / gas processing, and to an oil country tubular goods threaded joint having this coating structure as a lubricating coating. One of the features of this embodiment is the solid lubricating coating formed on the fastening surfaces of the threaded joint. However, the present disclosure does not impose any particular limitations on the structure of the threaded joint itself, and the structure of the threaded joint may be any known or novel structure.

[0029] <Oil well pipes and oil well pipe threaded joints> An oil country tubular good is made up of a box 2 such as a coupling, and a pin 1, as shown in FIG. As shown in FIG. 1, an oil well pipe threaded joint comprises a box 2, such as a coupling, having a female thread 2a, and a pin 1 having a male thread 1a. In this embodiment, a resin coating based on the present disclosure is formed on the outermost surface of the contact surface (fastening surface) of the threaded portion of at least one of the box 2 and the pin 1 (see FIG. 2).

[0030] Here, the resin coating 31 of this embodiment constitutes the outermost layer when the lubricating coating for the threaded portion is composed of multiple layers. That is, when the lubricating coating has a multi-layer structure as shown in FIG. 2, the resin coating 31 of this embodiment is not applied to the film inside the outermost layer (see FIG. 2(a)). In FIG. 2(a), reference numeral 30 denotes another solid lubricating coating or a base layer formed below the resin coating 31. There may be multiple lubricating films below the resin coating 31.

[0031] The main purpose of forming the resin coating 31 of the present disclosure is to reduce rattle in step 1 described above. It is assumed that the lubricity in step 2 depends on another solid lubricant coating. For this reason, in this embodiment, it is assumed that another solid lubricant coating is formed on either the pin thread or the box thread, or both. Then, for example, the resin coating 31 of the present disclosure is formed on one of the other solid lubricant coatings that have been formed.

[0032] Alternatively, if another solid lubricant coating is formed on only one of the pin threads or the box threads, the resin coating 31 of the present disclosure is formed on the thread surface that is not formed with the other solid lubricant coating. However, the resin coating 31 of the present disclosure can also be formed directly on the surface of the threaded portion of the oil well tubular good and used simply as an anti-rust coating for pin threads and box threads. Also, for repair and surface protection, a paint for forming the resin coating 31 of the present disclosure can be applied and the resin coating 31 can be formed as a top coat layer.

[0033] <Paint> The paint for forming the resin coating 31 in this embodiment is made of an alkali soap as a solid lubricant and a binder resin dissolved in an organic solvent. This paint is applied to the threads that make up the oil well pipe threaded joint. The coating liquid is then dried while being heated as necessary, to obtain the resin coating 31.

[0034] <Organic solvent> As the organic solvent, an organic solvent other than a lower alcohol (having 5 or less carbon atoms) is selected. If a lower alcohol is selected, the affinity with the binder resin described below is poor, and a homogeneous resin coating 31 cannot be formed. The organic solvent to be used is not particularly limited as long as it is not a lower alcohol. However, taking into consideration the application on an oil well pipe thread manufacturing line and the application during oil well pipe tightening work in a well, which require high productivity, it is preferable that the organic solvent to be used is a fast-drying, highly volatile solvent. Specifically, it is preferable that the organic solvent to be used is a material with a boiling point of 60°C or less.

[0035] Furthermore, a high flash point is desirable in consideration of safety in wells during the formation of the resin coating 31. Specifically, the organic solvent used is preferably a material with a flash point of 60° C. or higher. Solvents that satisfy these conditions include fluorine-based solvents, such as so-called alternatives to fluorocarbons, i.e., HFCs (hydrofluorocarbons), HFEs (hydrofluoroethers), HFOs (hydrofluoroolefins), and PFCs (perfluorocarbons).

[0036] <Binder resin> The binder resin plays a role in holding the alkali soap, which functions as a solid lubricant, on the threads of the oil country tubular goods. This means that the alkali soap contained in the formed resin coating 31 will not be washed away even if the oil country tubular goods is placed vertically or exposed to running water. Furthermore, when dissolving or dispersing a solid lubricant in a binder resin, a homogeneous dissolution or dispersion is generally desired, so it is common to select a material that has a high affinity for the solid lubricant, i.e., a material with a similar SP value, as the binder resin.

[0037] In contrast, in this embodiment, a binder resin that is intentionally poorly compatible with the alkaline soap is selected, which allows the alkaline soap to concentrate on the surface when the paint is applied, that is, the alkaline soap to automatically rise to the surface, forming an alkaline soap layer 31A with a high lubricating effect on the coating surface. From this viewpoint, in this embodiment, the binder resin has an SP value of 10.0 cal / cm 3 The following binder resins are used:

[0038] Here, the binder resin includes not only a single resin but also a composite resin. Even for the same type of resin, the SP value varies depending on the molecular weight and the type and number of functional groups, so it cannot be said that any resin satisfies the above-mentioned SP value. Examples of resins with relatively low SP values ​​include fluororesins and polyethylene. In addition, the SP value of the binder resin is 10.0 cal / cm 3 The following measures will increase the hydrophobicity and water resistance of the resin itself, and also improve its rust prevention properties. Moreover, it is preferable that the binder resin has high water repellency.

[0039] Conversely, the SP value of the binder resin is 10.0 cal / cm 3 If the temperature exceeds this range, the rust-preventive properties of the resin itself will decrease, and the deliquescent alkali soap will be more likely to disperse into the resin below the alkali soap layer 31A. As a result, the binder resin will no longer have sufficient rust-preventive properties. Here, there is no particular lower limit for the SP value of the binder resin, but it is set to, for example, 5.0 or more. Here, when the molecular structure is known, the Fedors method may be used to calculate the SP value, whereas when the molecular structure is unknown, the turbidimetric titration method may be used.

[0040] Furthermore, it is preferable that the binder resin has an average molecular weight of 10,000 or more and 300,000 or less. If the average molecular weight is too low, the affinity with the alkaline soap increases, making it difficult to obtain a stable alkaline soap layer 31A on the surface. On the other hand, if the average molecular weight is too high, more than 300,000, the hardness of the resin increases, making it difficult to uniformly apply paint to the thread surface, and there is a risk of impairing the lubricating effect of the alkaline soap in the above-mentioned step 1.

[0041] <Alkaline soap> In this embodiment, an alkaline soap is used as the solid lubricant. In the present disclosure, the alkaline soap refers to a salt of a fatty acid and an alkali metal such as sodium or potassium. In other words, the alkaline soap in this specification does not include metal soaps, which are salts of fatty acids and metals other than alkali metals. There is no particular restriction on the type of fatty acid that constitutes the alkaline soap. Representative fatty acids include stearic acid, palmitic acid, myristic acid, lauric acid, behenic acid, octanoic acid, oleic acid, linoleic acid, linolenic acid, ricinoleic acid, and 12-hydroxystearic acid.

[0042] In the present disclosure, the alkali metals constituting the alkali soap are substantially only sodium and potassium. Other alkali metals exist, but they are not usually available in the form of alkali soaps, or, like lithium, are more similar in nature to alkaline earth metals (metal soaps as salts with fatty acids). These alkali metals are not included in the alkali metals that make up the alkali soaps in this specification. That is, alkali metals include lithium, rubidium, and cesium, but the salts of these alkali metals are not included in the soaps (alkali soaps) of this disclosure.

[0043] In reality, it is not realistic because rubidium and cesium alkaline soaps are hardly available. Also, lithium soap is used as a thickener mixed into grease, rather than as a cleaning element like sodium and potassium, so it is not used for lubrication purposes itself. The weight of the alkaline soap is preferably 0.01 to 3 times the weight of the binder resin.

[0044] The resin coating 31 of this embodiment exhibits higher lubricating performance than other lubricants due to the alkaline soap being concentrated on the surface layer of the resin coating 31, thereby reducing coating damage caused by rattle before the oil well pipe threads engage. To achieve this effect, it is preferable to add at least 0.01 times the weight of the binder resin. On the other hand, if there is too much alkaline soap, it may prevent the formation of a homogeneous resin coating 31 and deteriorate the rust prevention properties. For this reason, it is preferable to set the upper limit of the amount of alkaline soap to be added at 3 times the weight of the binder resin. It is more preferable that the weight of the alkaline soap is 0.1 to 2 times the weight of the binder resin.

[0045] <Other additives> The paint for forming the resin coating 31 of this embodiment may contain additives other than the alkaline soap for the purpose of improving lubricity and rust prevention. For example, PTFE, metal soap, graphite, or the like may be added as another solid lubricant to improve the galling resistance exhibited after the oil well pipe is threadedly engaged. In this case, it is preferable to use a solid lubricant having a lower SP value than the alkali soap or a lubricant having a heavier mass than the alkali soap as the other solid lubricant, so that the other solid lubricant does not concentrate on the surface layer side of the resin coating 31. Alternatively, zinc phosphate or aluminum phosphate may be added as a rust inhibitor to further improve corrosion resistance during long-term storage.

[0046] <Application method> The method of applying the paint of this embodiment to the threaded portion of the oil well tubular goods is not particularly limited. Examples of application methods include spray application, brush application, immersion, etc. In order to form a uniform coating, spray application is preferred. In addition, it is preferable to rotate the oil well tubular goods at a constant speed during application and drying. This forms the resin coating 31 according to the present disclosure. In this resin coating 31, as shown in FIG. 2, the alkaline soap is concentrated on the surface side, and an alkaline soap layer 31A is formed on the surface as shown in FIG.

[0047] In this embodiment, "the alkaline soap is concentrated on the surface side" means that 70 wt % or more of the alkaline soap contained in the resin coating 31 is located on the upper half side (surface side) of the resin coating 31. It is preferable that 90 wt % or more is located on the upper half side (surface side) of the resin coating 31. In this way, the above-mentioned alkaline soap layer 31A is formed by the alkaline soap contained in the binder resin being concentrated and dispersed on the surface side. As a method for concentrating the alkaline soap on the surface side, in addition to adjusting the SP value of the binder resin, it is good to rotate the coated oil country tubular goods at a constant speed when applying and drying the paint for the resin coating 31. Furthermore, in order to obtain a stable alkaline soap layer 31A, natural drying is preferable to forced drying.

[0048] The concentration of the alkali soap on the surface side can be confirmed by quantifying the alkali metal in the alkali soap using, for example, EDX (energy dispersive X-ray analysis). This can be confirmed by the distribution of the alkali soap in the film thickness direction. This can be done, for example, by cutting out an arbitrary film thickness cross section of the threaded part after the film is formed, and measuring the concentration of the alkali metal (sodium or calcium) at equal intervals in the film thickness direction using EDX. This confirmation can be determined, for example, by calculating the average concentration in the upper half of the film thickness relative to the average concentration in the entire film thickness.

[0049] <Hardness of resin coating 31> The resin coating 31 formed by the above-mentioned method is preferably soft, with a pencil hardness of no greater than F. The hardness of the resin coating 31 is determined mainly by the binder resin. It is believed that by using such a soft resin coating 31, the film is appropriately scraped off at the stage where rattle occurs before the oil country pipe threads engage, allowing the alkali soap layer 31A to exhibit its lubricating properties. The pencil hardness of the resin coating 31 is more preferably 3B or less. The pencil hardness of the resin coating 31 also includes 6B or less.

[0050] Conversely, if the pencil hardness of the resin coating 31 is too high, the effect of reducing rattle may not be obtained. Furthermore, if the resin coating 31 peels off due to tightening of the screws, it may not be broken into small pieces and may cause clogging, which may result in the risk of galling. Here, the pencil hardness is measured in accordance with the standard JIS K 5600-5-4. The pencil hardness of the resin coating 31 can be adjusted mainly by changing the average molecular weight of the binder resin.

[0051] <Film thickness of resin coating 31> The thickness of the formed resin coating 31 is preferably in the range of 3 μm to 50 μm. If the thickness is thinner than 3 μm, sufficient lubricity and rust prevention cannot be obtained. On the other hand, if the thickness is thicker than 50 μm, excessive cutting debris is generated during screw tightening, which may cause seizure of the screw.

[0052] (Actions and others) As mentioned above, the lubrication behavior of oil country pipe threads can be roughly divided into the following two steps. Step 1: This is the stage from when the pin screw is inserted into the box screw to when the screws engage. This corresponds to the (x) area in Figure 5(a) during step 1 where there is initial wobble in Figure 4(a). Step 2: After the screws engage, they come into strong contact and tighten.

[0053] During the loosening process, this process is reversed; the screws come into strong contact with each other, then loosen until they stop interlocking (Step 2), and the pin screw and box screw no longer interlock tightly, and have some play (backlash) as they loosen (Step 1). In the tightening of OCTG threaded joints, when the threads of the pin and box are not yet engaged (step 1), rattle, i.e., eccentricity and whirling of the OCTG, occurs. This rattle causes damage to the solid lubricant coating formed on the threads.

[0054] In contrast, in this embodiment, in order to suppress this damage, a resin coating 31 having an alkali soap layer 31A on its surface is formed directly on the thread surface of at least one of the pin or box, or on the solid lubricant coating. The alkali soap layer 31A suppresses damage to the solid lubricant coating at the stage (step 1) when the threads of the pin and box are not engaged. That is, in this disclosure, when there is a "play" until the threads engage in step 1, the alkali soap on the surface of the resin coating 31 ensures "lubrication" that "slides" into a stable position of the thread. That is, the alkali soap has the effect of enhancing the overall lubrication by supporting a sliding lubrication that guides the threads to a position close to the original thread engagement position when tightening in a rattling state, which occurs in the initial stage of tightening of oil well pipe threads.

[0055] If the solid lubricating coating 30 formed on either one or both threads is not damaged during make-up in an area where there is initial thread play, the original lubricating properties can be maintained, and as a result, the number of make-up and unmake-up cycles can be stabilized. Here, metal soaps have been used as solid lubricants for oil country pipe threaded joints, and alkali soaps have not attracted attention. This is because alkali soaps are water-soluble and have poor waterproof and rust-proofing properties. Also, metal soaps are more easily dispersed in general binder resins.

[0056] In contrast, in this embodiment, it has been found that by intentionally adding an alkaline soap to the solvent in which the resin is dissolved, an alkaline soap layer 31A is formed on the surface layer of the resin coating 31, which is effective in reducing the above-mentioned rattle. This effect is particularly effective when the weight of the alkaline soap contained in the resin coating 31 is 0.01 to 3 times the weight of the resin constituting the resin coating 31. This allows the other solid lubricant coating 30 to exhibit sufficient galling resistance in the make-up process (step 2) after the threads are engaged.

[0057] On the other hand, even if a metal soap is added to the solvent in which the resin is dissolved instead of an alkali soap, a stable metal soap layer is not formed on the surface of the resin film, and the effect of reducing rattle is limited. Also, the binder resin functions as a binder for the alkali soap. Therefore, even if the oil well pipe is placed vertically after the coating is applied, or even if the oil well pipe is exposed to rain or backflow of muddy water, peeling or washing away of the alkali soap layer 31A can be suppressed. Furthermore, the binder resin has an SP value of 10.0 cal / cm 3 By selecting the following resin, a stable alkaline soap layer 31A can be formed on the surface of the resin film, and the rust prevention required for oil country tubular goods can also be obtained. If the SP value of the binder resin is too high, the resin will have a high affinity with alkaline soap and water, and the alkaline soap will disperse inside the resin film. In this case, the film as a whole will have a high deliquescence, which will induce rust.

[0058] The inventors have also found that if the resin coating 31 is too hard, i.e., if its pencil hardness exceeds F, the above-mentioned rattle suppression effect may not be sufficiently obtained even if an alkali soap is added. This is presumably because the binder resin supporting the alkali soap layer 31A becomes too strong, preventing the alkali soap layer 31A from sliding. Alternatively, it may be because the strong entanglement of polymers in the resin makes it difficult for the alkali soap molecules to move to the surface layer, making it impossible to obtain a stable alkali soap layer 31A.

[0059] (Other uses) As described above, the resin coating 31 of the embodiment is formed by applying and drying a paint made by dissolving an alkaline soap and a binder resin in an organic solvent. Therefore, the resin coating 31 is very easy to form. Therefore, if an already formed resin coating 31 or another lubricating coating is damaged, a repair process may be performed in which the paint of the embodiment is applied to the damaged area and dried. In this case, it is possible to repair the coating, and therefore the lubricity and corrosion resistance.

[0060] (others) The present disclosure may also have the following configuration. (1) An oil well pipe used in an oil well pipe threaded joint formed by connecting a box having a female thread and a pin having a male thread, the box or pin being constituted by the oil well pipe, The outermost layer of the threaded portion has a resin coating containing an alkali soap as a solid lubricant in a binder resin. The resin coating has an alkaline soap layer formed on the surface. (2) The alkaline soap contained in the resin coating is concentrated on the surface side to form the alkaline soap layer. (3) The above binder resin has an SP value of 10.0 cal / cm 3 The following is the result. (4) The weight of the alkaline soap is 0.01 to 3 times the weight of the binder resin. (5) The resin coating has a pencil hardness of F or less. (6) Under the resin coating, there is another solid lubricant coating. (7) An oil well pipe threaded joint formed by connecting a box having a female thread and a pin having a male thread, At least one of the box and the pin is made of the oil country tubular good of the present disclosure. (8) A coating material for forming a top layer on a threaded portion of an oil well pipe, comprising: The composition includes a solvent, a binder resin, and a solid lubricant. The solid lubricant contains an alkaline soap, The above binder resin has an SP value of 10.0 cal / cm 3and the average molecular weight is 10,000 or more and 300,000 or less, The weight of the alkaline soap is 0.01 to 3 times the weight of the binder resin. EXAMPLES

[0061] Next, examples based on this embodiment will be described. (About the laboratory test method) Conventional laboratory testing conditions are usually a vertical power tong method using a short pin of about 1m in length. Conventionally, the test was started at the position where the screw was tightened as much as possible by hand. In contrast, in the following examples, new laboratory test conditions are adopted, and a weight is placed on top of a short pin about 1 m long, and a tightening and tightening test is performed using a vertical power tong. A weight equivalent to the weight of 1 to 3 pins in an actual well is used as the weight. The reason is as follows. In the example where a short pin is used, the environment that occurs in an actual well that this disclosure is targeting, most evaluation results are considered to be pass, and it is not possible to truly select pass / fail. This is because even under conditions that would be considered pass, there are many cases where the result is NG when used in a well.

[0062] To repeat, in this disclosure, as described above (for example, see FIG. 2), the phenomenon occurring in the lubrication of oil well pipe threads is considered to be divided into the following two. That is, the inventors have found that it is important to evaluate thread lubrication including the make-up / unmake (lubrication) in the first stage (step 1) and the lubrication in the second stage (step 2). If the evaluation is not made taking these two stages into consideration, it is highly likely that troubles will occur frequently in an actual well, even if the lab evaluation is OK. The new laboratory test conditions make it possible to simulate and evaluate these two stages of lubrication, as may occur in actual wells, and clarify the meaning of the upper and lower limits defined in this disclosure.

[0063] The two-stage lubrication is the two steps of the (x) stage (step 1) and the (y) + (z) stage (step 2) in Figure 5(a). In an actual well, the initial set is not tightened to the level where the threads are completely engaged, and high-speed tightening at about 5-20 rpm is performed using power tongs. A large load of the full-length pin (40 feet ≒ 12 m) is applied to the box screw, and at the same time, there is a backlash because the threads are not engaged with each other. The pin threads and box threads may come into contact locally, causing considerable damage to the solid lubricant coating. This is the step 1 stage. When a clear torque is established, the tightening speed is reduced to about 0.5-3 rpm, depending on the type of thread, and tightening is performed until it is completely tightened. This is step 2. Back-tightening follows the reverse process.

[0064] A test apparatus simulating an actual well for carrying out the new laboratory test conditions will be described with reference to Figs. 6 and 7. The new laboratory test conditions are based on evaluation under feasible conditions of heavy load during tightening and uneven load during tightening and loosening. For example, a heavy load equivalent to a full-sized pin is applied, and in the process of tightening the screw, the rattle until the screws engage is taken into consideration. In addition, in the process of loosening the screw, the fact that the screws come out of engagement and rattle is taken into consideration. In the new laboratory test conditions, a vertical power tong 4 is used as shown in Figure 6. A short pin 1 is also used as the test pin. However, it is possible to apply and remove a load from a weight 3 on the top of the pin 1.

[0065] The short pin 1 and the box 2 are then fastened together by a pin screw 1a and a box screw 2a. At that time, in order to simulate a situation where the threads do not mesh, the initial temporary tightening position is set so that half of the total number of threads of the pin thread 1a are exposed from the box thread 2a (see Figure 4(b)). This is one of the causes of wobble. Tightening begins from that state. In addition, when fastening, a weight 3 is attached to the end of the pin 1 on the opposite side to the fastening screw for the box screw 2a. The weight of the weight 3 is calculated based on the actual size of the pins, such as their outer diameters and thicknesses, as a load equivalent to one to three actual size pins.

[0066] The weight 3 shown in Fig. 6 is composed of a weight body 3A and an insertion rod 13, as shown in Fig. 7. The insertion rod 13 is joined to the underside of the weight body 3A by welding, and is disposed in an axially symmetrical position of the weight 3. The insertion rod 13 is inserted loosely into the pin 1 to attach the weight to the pin. Reference symbol 1c indicates the inner diameter surface of the pin 1. When the weight 3 is attached as described above, holes 1d and 13a are previously drilled in the insertion rod 13 and the pin 1, which penetrate the pin 1 and the insertion rod 13. Then, as shown in Fig. 7, the weight 3 and the pin 1 are integrated by inserting the piercing rod 12 into the holes 1d and 13a. A swivel-type hook 11 is welded to the center of the shaft at the top of the weight 3, and the weight is suspended from a suspension device 20 on the ceiling via a hanging chain 21. This makes it possible to adjust the load of the weight on the pin by adjusting the degree to which the weight is suspended by the suspension device 20.

[0067] When tightening, the hanging chain 21 is loosened, the weight load is applied to the box screw, and the tightening is performed at 5 to 20 rpm until the torque is generated (Step 1). This is a simulation of wobble. Once the torque is generated, the rotation speed is reduced to 0.5 to 2 rpm, and the tightening is performed to the tightening position (Step 2). On the other hand, when loosening (re-tightening), the weight 3 is lifted by the hanging device 20, and re-tightening is performed without applying the weight of the weight 3. When the torque is high, the rotation speed is set to 0.5 to 2 rpm to start loosening. Then, when the torque reaches about 1 / 10 of the tightening torque value, the loosening is started at a high speed of 5 to 20 rpm. This makes it possible to conduct laboratory tests under conditions close to those of an actual well.

[0068] (About oil well pipe thread joints) The oil well pipes were prepared as a pipe body (pin) with an outer diameter of 244.48 mm, a wall thickness of 13.84 mm, and steel grade API5CT Q125, and a corresponding coupling (box). A premium joint for oil well pipes with a thread pitch of 5.08 mm was used for the thread joint. Further, the pin thread was formed with a resin coating 31 based on the present disclosure or a comparative resin coating 31. The box thread was formed with a solid lubricant coating mainly made of PTFE, which is different from the resin coating 31 of the present disclosure. Then, a tightening / loosening test was conducted under the new laboratory test conditions described above to evaluate galling resistance. At this time, the hand tightening was stopped when the pin thread protruded 8 threads from the box, and further, a weight of 3 tons (approximately the weight of three 12 m pipes of the same size) was placed on the pin thread pipe to intentionally create a rattle at step 1.

[0069] (Evaluation: number of times tightening and loosening) Each threaded joint was evaluated based on the number of times it could be tightened and loosened without galling to a level that could not be repaired, and a joint that could be tightened and loosened five times or more was considered to have passed. According to the API5C5 standard, the half hand tight and application of weights as described above are not required, and for the size of the oil well pipe used in this embodiment, if it can be tightened and tightened three times without galling, it is considered to pass. However, here, the pass standard is stricter in order to pursue higher galling resistance. Note that if the number of tightening and tightening reaches 10 times, the test is stopped regardless of whether galling occurs or not.

[0070] (Evaluation: Rust prevention) In addition to the above tests, a cut sample of the pin thread portion of a pipe body with an outer diameter of 88.90 mm, a wall thickness of 6.45 mm, and steel grade API5CT L80 was also prepared. A premium joint for oil well pipes with a thread pitch of 4.23 mm was used as the pin thread, and the resin coating 31 of the present disclosure or a comparative resin coating 31 was formed on the thread surface to produce each sample. The salt spray test specified in JIS K 5600-7-1 was carried out for eight hours on these materials, and the rust resistance was evaluated by checking whether or not rust occurred. Here, no rust was given 5 points, rust (area rate 1% or less) was given 4 points, rust (area rate over 1% and 10% or less) was given 3 points, rust (area rate over 10% and 50% or less) was given 2 points, and rust (area rate over 50%) was given 1 point, and a score of 4 or more was considered a pass.

[0071] Table 1 shows the test conditions and evaluation results.

[0072] [Table 1]

[0073] In Table 1, P / B indicates the weight ratio of the solid lubricant (alkali soap) to the binder resin. The main difference between saturated polyester A and saturated polyester B in Table 1 is the hydroxyl value. That is, saturated polyester A had a hydroxyl value of 10 [KOHmg / g] or less. Saturated polyester B had a hydroxyl value of about 100 [KOHmg / g]. The fluororesin A used had an average molecular weight of about 30,000, and the fluororesin B used had an average molecular weight of about 200,000. As the organic solvent, HFO, toluene, or MEK was used as shown in Table 1.

[0074] Comparative Example 1 Comparative Example 1 has an SP value of 10.0 cal / cm 3 The following resin coating 31 is used. However, this is an example in which the resin coating 31 does not contain alkaline soap. The conditions of Comparative Example 1 were used as the standard for evaluation. The resin coating 31 of Comparative Example 1 had a pencil hardness of B. In Comparative Example 1, the rust prevention was satisfactory with a score of 5, but the number of times of tightening and loosening was 2, resulting in a failure.

[0075] (Examples 1 to 4) In Examples 1 to 4, sodium stearate was used as the alkaline soap contained in the resin coating 31, and the test was carried out to confirm the effect of its concentration. In Examples 1 to 4, the pencil hardness was B or 2B. As can be seen from Examples 1 to 4, when the P / B value, which indicates the ratio of the weight of the solid lubricant to the weight of the binder resin, was in the range of 0.01 to 3, the number of tightening and loosening operations was judged to be acceptable in all cases. Here, even a small amount of alkaline soap can be added to improve galling resistance. However, it can be seen that a greater effect can be obtained by increasing the amount of alkaline soap added. This is because the lubricating properties of the alkaline soap reduce damage to the solid lubricant film on the threads caused by the backlash in step 1.

[0076] On the other hand, it can be seen that the rust prevention performance is slightly reduced when the P / B value is increased to 3. This is thought to be because there are too many additives, making it difficult to form a dense and uniform resin coating 31. From these results, it is understood that the P / B value should be 0.01 or more and 3 or less. The P / B value is preferably 0.1 or more and 2 or less, and more preferably 0.5 or more and 1.4 or less. In view of this, P / B=1 was set in the following examples and comparative examples.

[0077] Comparative Example 2 Comparative Example 2 is a test in which a metal soap, more specifically, calcium stearate, was added instead of the alkaline soap. In Comparative Example 2, the pencil hardness was 2B, which was the same as in Example 3. However, in Comparative Example 2, the rust prevention was satisfactory with a score of 5, but the number of tightening and loosening was 4. That is, in Comparative Example 2, the galling resistance was significantly reduced compared to Example 3 in which alkaline soap (sodium stearate) was added. This is because calcium stearate is dispersed within the resin coating 31, and a stable soap layer is not formed on the surface of the film as with sodium stearate.

[0078] Example 5 Example 5 is an example in which a binder resin different from those in Examples 1 to 4 was selected. Specifically, the SP value was even lower (7.6 cal / cm 3 As a result, the number of times of tightening and loosening and the rust prevention properties were the highest, along with Example 3.

[0079] (Comparative Examples 3 and 4) Comparative Examples 3 and 4 are examples in which the SP value of the binder resin is high. In Comparative Example 3, a saturated polyester resin different from those in Examples 1 to 4 was used. In Comparative Example 4, nitrocellulose was used. The SP value of Comparative Example 3 was 11.9 cal / cm 3 , and the SP value of Comparative Example 4 was 13.0 cal / cm 3 It was. Although both Comparative Examples 3 and 4 met the pass criteria for the number of tightening and loosening operations, they were found to be inferior to Example 3, which had the same P / B value and a low SP value. Moreover, Comparative Examples 3 and 4 were unsuccessful in terms of rust prevention, with scores of 3 and 2, respectively.

[0080] This shows that if the SP value of the binder resin is too high, both galling resistance and rust prevention properties decrease. 3 It is estimated that good galling resistance and rust prevention properties can be obtained if the content is below this range. It should be noted that the pencil hardness of the resin film 31 in Comparative Example 4 was considerably higher than that in Example 3, which may have also had an effect. In other words, it is considered possible that the resin film 31 that is too hard may inhibit the sliding of the alkaline soap layer 31A.

[0081] Comparative Example 5 Comparative Example 5 is an example in which the pencil hardness of the resin coating 31 is high. Comparative Example 5 achieved a pencil hardness of 3H by using a fluororesin different from that used in Example 5. Comparative Example 5 had an SP value of 6.7 cal / cm 3Although the number of times of tightening and loosening was only four, which is very low as in Example 5. This also shows that the lubricating effect of the alkali soap layer 31A cannot be sufficiently obtained unless the pencil hardness of the resin coating 31 is kept low. From the results of Example 5, it is considered that it is good to keep the pencil hardness at F or less.

[0082] The entire contents of Japanese Patent Application No. 2022-134377 (filed on August 25, 2022), from which this application claims priority, are incorporated herein by reference. Although the present application has been described with reference to a limited number of embodiments, the scope of the rights is not limited thereto, and modifications of each embodiment based on the above disclosure would be obvious to one skilled in the art. [Explanation of symbols]

[0083] 1 pin 1a Male thread 2 Box (coupling) 2a Female thread 3 weight 3A Weight body 4. Power Tong 12 Piercing Rod 13 Insert rod 20 Lifting equipment (crane) 21 Chain (hanging rope) 30 Other solid lubricant coatings 31 Resin coating 31A Alkaline soap layer

Claims

1. An oil well pipe used in an oil well pipe threaded joint in which a box having a female thread and a pin having a male thread are connected to each other, the oil well pipe constituting the box or pin, The outermost layer of the threaded portion has a resin coating containing an alkali soap as a solid lubricant in a binder resin. The resin coating has an alkaline soap layer formed on the surface thereof, When the resin coating is divided at the center in the thickness direction into an upper half side and a lower half side which are surface sides, the alkali soap layer is formed on the upper half side, the upper half side contains 70 wt % or more and less than 100 wt % of the alkali soap contained in the resin coating, and both the upper half side and the lower half side contain a binder resin. Oil country tubing.

2. The alkaline soap contained in the resin coating is concentrated on the surface side to form the alkaline soap layer.

2. An oil country tubular good according to claim 1.

3. The binder resin has an SP value of 10.0 cal / cm 3 2. An oil country tubular good according to claim 1, wherein:

4. 2. The oil country tubular good according to claim 1, wherein the weight of the alkali soap is 0.01 to 3 times the weight of the binder resin.

5. 2. The oil country tubular good according to claim 1, wherein said resin coating has a pencil hardness of F or less.

6. 2. The oil country tubular good according to claim 1, further comprising another solid lubricant coating below said resin coating.

7. An oil well pipe threaded joint formed by connecting a box having a female thread and a pin having a male thread, At least one of the box and the pin is made of the oil well tubular good according to any one of claims 1 to 6. Oil well pipe threaded joints.

Citation Information

Patent Citations

  • Composition for forming lubricating film suitable for lubrication treatment of screw joint

    JP2002173692A

  • Thread coupling for steel pipes

    JP2004053013A

  • Threaded joints for steel pipes

    JP2008537062A

  • Dry wire drawing lubricant

    JP2009132811A

  • Tubular threaded joint excellent in high torque performance

    JP2013108556A